Impact of N, P, K, and Humic Acid Supplementation on the Chemical Profile of Medical Cannabis (Cannabis sativa L) - Bernstein, Nirit; Gorelick, Jonathan; Zerahia, Roei; Koch, Sraya (Frontiers in Plant Science, 2019)
Mineral nutrition is a major factor affecting plant growth and function. Increasing evidence supports the involvement of macro and micronutrients in secondary metabolism. The use of appropriate nutritional measures including organic fertilizers, supplements, and biostimulants is therefore a vital aspect of medicinal plant production including medical cannabis. Very little information is available concerning the effects of nutritional supplements on physiological and chemical properties of medical-cannabis, and their potential role in standardization of the active compounds in the plant material supplied to patients. This study therefore evaluated the potential of nutritional supplementations, including humic acids (HA) and inorganic N, P and K to affect the cannabinoid profile throughout the plant. The plants were supplemented with HA, enhanced P fertilization, or enhanced NPK. The results demonstrate sensitivity of cannabinoids metabolism to mineral nutrition. The nutritional supplements affected cannabinoid content in the plants differently. These effects were location and organ-specific, and varied between cannabinoids. While the P enhancement treatment did not affect THC, CBD, CBN and CBG concentrations in the flowers from the top of the plants, a 16% reduction of THC concentration was observed in the inflorescence leaves. Reduced CBN concentrations were only seen in flowers from the lower part of the plants. Enhanced NPK and HA treatments also produced organ specific and spatially specific responses in the plant. NPK supplementation increased CBG levels in flowers by 71%, and lowered CBN levels in both flowers and inflorescence-leaves by 38% and 36%, respectively. HA was found to reduce the natural spatial variability of all of the cannabinoids studied. However, the increased uniformity came at the expense of the higher levels of cannabinoids at the top of the plants, THC and CBD were reduced by 37 and 39% respectivelyChanges in mineral composition were observed in specific areas of the plants. The results demonstrate that nutritional supplements influence cannabinoid content in cannabis in an organ and spatial dependent manner. Most importantly, the results confirm the potential of environmental factors to regulate concentrations of individual cannabinoids in medical cannabis. The identified effects of nutrient supplementation can be further developed for chemical control and standardization in cannabis.